Analysis and Prospects of Using Recombinant Vaccinia Virus MVA Strain as a Vector in the Development of the Vaccines against Human and Simian Immunodeficiency Virus Diseases - L. F. Stovba; V. T. Krotkov; D. I. Paveli’ev; S. A. Mel’nikov; V. N. Lebedev; S. V. Borisevich (Проблемы особо опасных инфекций, 2019)
The review presents the results of preclinical use of vector vaccines against human immunodeficiency virus (HIV) disease and simian immunodeficiency virus (SIV) disease. Application of antiretroviral therapy exclusively is insufficient for elimination of HIV from patient’s body. This dictates the need for an effective vaccine which will reduce the number of new cases of the disease and reduce the risk of virus transmission. Current practice of medicinal product development showed the effectiveness of heterologous prime-boost regimens for the induction of expressed immune response in laboratory animals. Various vector constructs were used as priming vaccines: DNA vaccines, Bacille Calmette-Guerin vaccine, chimpanzee adenovirus, vesicular stomatitis virus, alphavirus repli-clone. Booster vaccine was represented by recombinant MVA strain. In all vector vaccines, different genes of immunodominant antigens of HIV and SIV agents were inserted. On rhesus macaques, murine, rabbit models, it was demonstrated that deployed vaccination schemes were safe and induced immune response. Because membrane HIV protein is highly variable, strongly glycoziled and subjected to structural changes during receptor binding, it cannot be viewed as a target for induction of virus neutralized antibodies. Therefore, we mainly studied the cell immune response that was presented by poly-functional CD8+ T-cells. However, some recent researches are aimed at such modification of envelope HIV immunogene that would provide for virus neutralizing antibody induction. The study of protective efficiency of the induced immunity in rhesus macaques, immunized with recombinant vectors expressing SIV’ s immunodominant antigens, in case of subsequent inoculation with virulent SIV strain has revealed that all monkeys developed illness. Assuming that the constructions with SIV’ s immunodominant antigens under protective efficiency testing on rhesus macaques imitate AIDS in humans, it seems that vaccines, developed up-to-date, will not be effective for collective immunity formation against AIDS. Therefore, the search for novel combinations of expressed immunodominant antigens for the inclusion into the composition of priming and booster vaccines remains a priority area at present time.